(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: C-reactive protein is a biomarker among the spontaneous intracerebral haemorrhage patients. Objective: The purpose of this present study was to see the association of CRP level with the short term clinical outcome among spontaneous intracerebral haemorrhage patients. Methodology: This prospective cohort study was conducted in the Department of Neurology at Dhaka Medical College and Hospital, Dhaka, Bangladesh from July 2012 to June 2014 for a period of two (02) years. Patients presented with first ever spontaneous intracerebral haemorrhage with the age group of more than or equal to 18 years with both sexes and hospital admission within 48 hours of onset were included for this study. Admission plasma CRP was measured and study population were divided into group I (plasma CRP≥6 mg/L) and group II (plasma CRP<6 mg/L). The patients were observed daily till 1 week after admission with special attention to vital parameters and clinical outcome which were mortality, functional outcome and early neurological worsening. Finally findings were analyzed and clinical outcome were compared in patient with different level of admission plasma CRP. Result: Early neurological worsening at the end of first week was 37(38%) patients. Poor functional outcome (GOS 2-3) at the end of first week was found in 51(52%) patients. Overall mortality within that period was 16(17%) patients. Elevated CRP level was associated with higher proportion of GCS score < 9 at day seven. Early neurological worsening and poor functional outcome (GOS2-3) was also found more in these patients. Conclusion: High admission plasma CRP level may be associated with higher proportions of poor short term outcome (GOS 2-3), early neurological worsening at the end of the first week after onset and mortality within this period in the patients with spontaneous intracerebral haemorrhage. Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 89-93